Pengetahuan Remaja tentang Kesehatan Pembuangan Kotoran pada Manusia - Rianti, Emillia Devi Dwi; Hutami, Gandes; Alvina, Adella; Putri, Resa; Syintia, Vindy; Hardiyanti, Anindya (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2026)
Background: Improper disposal of human waste can cause environmental pollution, increasing the risk of infectious diseases such as diarrhea. Adolescents as an age group who are building awareness of healthy living have an important role in environmental sanitation management. Objective: is to describe the level of knowledge of adolescents regarding the health of human waste disposal. Methods: research with measurement of the level of knowledge in the form of a questionnaire as an instrument, the method used is descriptive quantitative with a sample of 30 respondents from students aged 17-19 years. Results: research from the level of knowledge with the distribution of understanding of good environmental health is: 40%, human waste disposal: 40% (good), human waste causes disease: 67% (good), prevention of diarrhea by washing hands: 67% (good), and the distance of septic tanks to water sources: 60% (sufficient). So obtained a fairly good level of knowledge. Conclusion: sufficient knowledge of disease prevention management, sufficient knowledge of environmental management to be clean and healthy disease prevention. Good knowledge of human waste can cause disease, and good knowledge of diarrhea prevention by washing hands, one of which is sufficient knowledge of septic tanks to clean water sources. Improper disposal of human waste can cause environmental pollution and increase the risk of infectious